WORDWALL LEARNING MEDIA TRAINING AT SMPN 3 SUMBER AS A CREATIVE SOLUTION IN THE DIGITAL ERA - Mimin Darmini; Regina Kezia Anggraeni Situmorang; Rezwandy Wahyudi Saputra; Ria Kusumawati; Ridha Nur Amaliyah (Ann Publisher, 2026)
Abstract: Background. The rapid development of digital technology requires educators to innovate in teaching to maintain student engagement. Aims. This community service program aimed to enhance teachers' competence in creating interactive learning media using the Wordwall platform. The training was held at SMPN 3 Sumber on December 14, 2024, and involved 40 teachers from various subjects. Methods. Activities were conducted using an andragogical approach, including interactive lectures, demonstrations, and hands-on practice. Result. The evaluation results showed a highly positive impact, with 96% of participants expressing satisfaction. Teachers appreciated the relevance of the materials (96%), the digital tools used (90.6%), and the instructors' effectiveness (95.8%). Moreover, 92.8% of participants demonstrated a very high understanding of the basic concepts of Wordwall. This training successfully improved teachers' digital literacy and their ability to design, engage, and effectively engage in interactive learning activities.